Hubungan Kualitas Makanan dengan Kejadian Stunting di Wilayah Kerja Puskesmas Kota Karang Bandar Lampung - Suci Nur indah Sari; Anita Bustami; Setiawati Setiawati (Malahayati Nursing Journal, 2024)
ABSTRACT Based on data situation and nutritional analysis in Indonesia, the proportion of very short and stunted children aged 0-59 months is 2.5% very short and 7.0% short. The 2021 Lampung Province nutrition survey for toddlers with very short nutritional status was 18.5%, this figure has decreased from the previous year, which was 26.26%. The prevalence of stunting under five in Lampung Province in 2021 is below the national figure, namely stunting under five by 24.4%.Resolving the relationship between food quality and the incidence of stunting in the work area of the Public Health Center Kota Karang Bandar Lampung in 2023. Type of quantitative research, with an analytic research design with a cross sectional approach. The population toddlers aged 3-5 years is 153 people, the sample is 86 respondents using simple random sampling method. Collecting data using questionnaires and using body scales and measuring height. The data analysis technique uses the Chi Square statistical test. Frequency distribution of Balita food quality, with unfavorable category as many as 49 respondents (57%). The distribution of the frequency of stunting in children under five, with the category of experiencing stunting, was 27 respondents (31.40%). There is a relationship between food quality and the incidence of stunting. p-value = 0.016. OR: 3,875. Based on the chi-square test, there is a relationship between food quality and the incidence of stunting among toddlers in the working area of the Karang Bandar Lampung City Health Center in 2023. Keywords: Food, Quality, Stunting  ABSTRAK Berdasarkan data situasi dan analisis gizi di Indonesia persentase sangat pendek dan pendek pada balita 0-59 bulan sebesar 2,5% balita sangat pendek dan sebesar 7,0% balita pendek. Survei gizi Provinsi Lampung tahun 2021 balita dengan status gizi sangat pendek sebesar 18,5%, angka ini mengalami penurunan dari tahun sebelumnya yaitu 26,26%. Prevalensi balita stunting di Provinsi Lampung tahun 2021 ini dibawah angka nasional yaitu balita stunting sebesar 24,4%. Diketahui hubungan kualitas makanan dengan kejadian stunting di wilayah kerja Puskesmas Kota Karang Bandar Lampung Tahun 2023. Jenis penelitian kuantitatif, dengan rancangan penelitian analitik dengan pendekatan cross sectional. Populasi ibu yang memiliki balita usia 3-5 tahun sebanyak 153 orang, sampel sebanyak 86 responden dengan metode simple random sampling. Pengumpulan data menggunakan lembar kuesioner dan menggunakan timbangan badan dan pengukur tinggi badan. Teknik analisis data menggunakan uji statistik Chi Square. Distribusi frekuensi kualitas makanan balita, dengan kategori kurang baik sebanyak 49 sresponden (57%). Distribusi frekuensi kejadian stunting pada balita, dengan kategori mengalami stunting sebanyak 27 responden (31,40%). Ada hubungan antara kualitas makanan dengan kejadian stunting. p value = 0,016. OR: 3,875. Berdasarkan uji chi-square terdapat hubungan antara kualitas makanan dengan kejadian stunting pada balita di wilayah kerja puskesmas kota karang bandar lampung tahun 2023. Kata Kunci: Kualitas, Makanan, Stunting